PREVALENCE OF ARTERIAL HYPERTENSION, ASSOCIATED DISEASES AND END-ORGAN DAMAGES IN REPUBLIC OF BASHKORTOSTAN - T. V. Lukmanova; I. M. Karamova; N. H. Sharafutdinova (Рациональная фармакотерапия в кардиологии)
Aim. To estimate arterial hypertension (AH) prevalence among population of Republic of Bashkortostan (RB), prevalence of end-organ damages and the associated clinical conditions in hypertensive patients.Material and methods. 1648 people from 10 regions of RB were examined. Standard questionnaires were used - socially-demographic, health condition, WHO cardiologic questionnaire, women’s health.Results. The urban and rural AH prevalence, AH prevalence in men and women, as well as AH comorbidities prevalence is studied. There is a high frequency of myocardial infarction and cerebral strokes in AH patients. Prevalence of end-organ damage and the associate clinical conditions is various in men and in women.Сonclusion. Available data will help to develop primary and secondary AH prevention taking into account risk factors.